2024
DOI: 10.1111/psj.12532
|View full text |Cite
|
Sign up to set email alerts
|

The interactive effects of policies: Insights for policy feedback theory from a qualitative study on homelessness

Anna Kopec

Abstract: The policy feedback literature has long argued that policies influence politics. Several scholars have examined the interpretive and resource effects of policies on political participation. However, how different policy design characteristics – say their generosity and their delivery – interact to influence political engagement requires further attention. This article demonstrates that policy characteristics within and between policies interact and can have counteracting or complementary effects on engagement.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…In speaking with individuals involved in various venues and processes, such as consultations with governments in Canada, Kopec (2022) found that tokenism and inequalities of participation influence experiences associated with such spaces. Participants pointed to the language used in some consultations that led to their exclusion, tokenism through similar individuals being asked to participate in campaigns and consultations without adequate compensation, and others having to make space for themselves to be heard (Kopec 2022(Kopec , 2024. At times, those that participate can feel as if their participation has no effect, with a lack of follow-up after their participation (Kopec 2022(Kopec , 2024Ilyniak 2022).…”
Section: Homelessness In Canadamentioning
confidence: 99%
See 1 more Smart Citation
“…In speaking with individuals involved in various venues and processes, such as consultations with governments in Canada, Kopec (2022) found that tokenism and inequalities of participation influence experiences associated with such spaces. Participants pointed to the language used in some consultations that led to their exclusion, tokenism through similar individuals being asked to participate in campaigns and consultations without adequate compensation, and others having to make space for themselves to be heard (Kopec 2022(Kopec , 2024. At times, those that participate can feel as if their participation has no effect, with a lack of follow-up after their participation (Kopec 2022(Kopec , 2024Ilyniak 2022).…”
Section: Homelessness In Canadamentioning
confidence: 99%
“…Participants pointed to the language used in some consultations that led to their exclusion, tokenism through similar individuals being asked to participate in campaigns and consultations without adequate compensation, and others having to make space for themselves to be heard (Kopec 2022(Kopec , 2024. At times, those that participate can feel as if their participation has no effect, with a lack of follow-up after their participation (Kopec 2022(Kopec , 2024Ilyniak 2022). Such attempts can recreate individualist approaches to homelessness that ignore structural issues and include a significant amount of work for individuals with LE that is rarely compensated or later included in policy (Ilyniak 2022).…”
Section: Homelessness In Canadamentioning
confidence: 99%